The birth of the state : ancient Egypt, Mesopotamia, India and China - Charvát, Petr, (Karolinum Press, 2013)
'The Birth of the State' provides an overview of four of the most significant cultural centres in the ancient world, now in Egypt, the Persian Gulf region, India, and China.